PENGARUH PENDIDIKAN PRANIKAH DENGAN MEDIA SOSIAL INSTAGRAM TERHADAP STATUS GIZI CALON PENGANTIN PEREMPUAN DI PUSKESMAS JATEN II KABUPATEN KARANGANYAR - Aprilia Rusvitasari; Megayana Yessy Maretta; Deny Eka Widyastuti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
Limited access to preconception health is due to their low knowledge of this aspect. Efforts to improve knowledge can be carried out by providing information about preconception health. This study aims to analyze the effect of premarital education through Instagram on the nutritional status of prospective brides and grooms. This study applies a pre-experimental method through a one-group pretest-posttest design. The research sample consisted of 40 prospective brides and grooms at the Jaten II Health Center who met the inclusion and exclusion criteria using the total sampling technique. The research instruments were questionnaires and Instagram. Data analysis was carried out univariately and bivariately, with bivariate analysis using the Wilcoxon test. The results showed that: 1) The characteristics of the respondents were mostly aged 20-35 years (87.4%), high school (45.0%), and private employees (40.0%). 2) Nutritional status based on BMI before premarital education was classified as underweight (100%), but after premarital education it increased to normal conditions (75.0%). Nutritional status based on Hb levels before premarital education was categorized as low (100%), but increased to normal (78.0%) after being given premarital education. There was a significant effect of premarital education through Instagram on the nutritional status of prospective brides and grooms at Jaten II Health Center (p-value 0.000 <0.05). The conclusion of this study is that premarital education through Instagram affects the nutritional status of prospective brides and grooms based on body mass index and Hb levels.